ChemInform Abstract: Synthesis of (Z)‐N‐Alkenyl‐β‐arylselanyl Imidazoles via Additive‐Free Nucleophilic Addition of Imidazole to Arylselanylalkynes. Issue 27 (8th July 2014) - Soares, Liane K.; Lara, Renata G.; Jacob, Raquel G.; Lenardao, Eder J.; Alves, Diego; Perin, Gelson
Abstract The addition proceeds with high regio‐ and E/Z‐selectivity to produce (Z)‐alkenes as only isomers.